2023
DOI: 10.1007/s40120-023-00439-y
|View full text |Cite
|
Sign up to set email alerts
|

Assisted Reproductive Techniques in Multiple Sclerosis: Recommendations from an Expert Panel

Abstract: Introduction: Multiple sclerosis (MS) is mainly diagnosed in women of reproductive age. However, there is a paucity of guidelines jointly prepared by neurologists and gynaecologists on managing women with MS and the desire for motherhood. Therefore, in this review we propose recommendations for such cases, with an particular focus on those requiring assisted reproductive techniques (ART).Methods: A group of seven MS experts (4 neurologists and 3 gynaecologists) came together for three discussion sessions to ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 67 publications
0
1
0
1
Order By: Relevance
“…Furthermore, recent studies suggest that in vitro fertilization (IVF) may not be linked with MS relapses, as previously proposed. This improvement in disease control during IVF could be explained, at least in part, by advancements in the treatment landscape for MS and better family planning [ 26 ]. In this vein, recent data has shown that continuing the use of disease-modifying therapy (DMT) until receiving a positive pregnancy test after IVF could help reduce the incidence of relapses [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, recent studies suggest that in vitro fertilization (IVF) may not be linked with MS relapses, as previously proposed. This improvement in disease control during IVF could be explained, at least in part, by advancements in the treatment landscape for MS and better family planning [ 26 ]. In this vein, recent data has shown that continuing the use of disease-modifying therapy (DMT) until receiving a positive pregnancy test after IVF could help reduce the incidence of relapses [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Como consecuencia, es frecuente que las pacientes tengan que posponer su deseo gestacional, y es habitual que haya un retraso en la edad a la que consiguen ser madres con respecto a la media en mujeres sanas [ 10 ]. Esto puede dar lugar a un incremento en el número de pacientes que tienen que recurrir a una técnica de reproducción asistida [ 12 ]. Habitualmente, la evolución de la enfermedad, en el caso de mujeres con EM que deciden quedarse embarazadas, es favorable, ya que la tasa anualizada de brotes disminuye significativamente durante este período para incrementarse ligeramente tras el parto y volver a estabilizarse con el tiempo hasta alcanzar niveles previos a la gestación [ 9 , 13 - 15 ].…”
Section: Introductionunclassified